Analysis of emergency response actions for preventing fire-induced domino effects based on an approach of reversed fuzzy Petri-net. (May 2017) - Zhou, Jianfeng; Reniers, Genserik
Abstract: In the chemical process industry, large quantities of different flammable substances are stored in tank farms. Due to potential mutual impacts among the tanks, severe domino accidents may occur after a tank catches fire. The emergency response to a tank fire may influence the development of the accident and impact the occurring of escalating events or so-called domino effects. In this paper, a fuzzy Petri-net (FPN) based reversed reasoning approach is proposed to analyze emergency response actions impacting domino effects. FPN is utilized to deduce the consequence-antecedent relationship between an accident and the emergency response actions. To analyze and compare the impacts of the actions on a domino effect, the backward reasoning is of special interest and often preferable when the occurrence probability of domino effects is known. As a tank fire accident in an oil depot usually lasts for a certain period of time, and as it may be greatly influenced by emergency response actions, it is taken as an example to illustrate the proposed approach. Highlights: Analysis of emergency response actions that might affect the domino effect. A reversed fuzzy Petri-net modeling approach for the emergency response process. Backward reasoning for the analysis of emergency response actions.